Predictive Ability Of Selected Individual And Organisational Variables On Job Performance Of Selected Employees In A Japanese Multinational Company In Malaysia - Devi Subramaniam, Indra (1996)
This study was designed to identify the variables that determine job performance of selected employees in a Japanese mutinational company in Malaysia. More specifically, the study sought to identify the significant predictors of job performance of the selected employees in this company. A total of 124 employees from execut:ive to clerical level were selected at random as respondents. A structured questionnaire was used as the research instrument. The study found that using the conceprual framework. of a direct relationship between the predictor variables and job performance to be reasonable since the model with the selected predictor variables was able to explain about 36 percent of the variation in job performance.